PERLINDUNGAN HUKUM TERHADAP ISTERI YANG MENJADI KORBAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA (KDRT) BERUPA PENELANTARAN DALAM RUMAH TANGGA DI POLRESTA PADANG - Rifqi Kurniawan dan Fitra Oktoriny (Fakultas Hukum Universitas Tamansiswa Padang, 2021)
The household is the smallest organization in society that is formed because of the existence of a marriage bond. Tensions and conflicts between family members are normal in the household. Conflicts between family members have resulted in domestic violence, various types of domestic violence are physical, psychological, sexual violence and domestic neglect. Many conflicts between family members stem from economic factors that lead to neglect in the household. The problem raised in this study is legal protection for wives who are victims of domestic violence (kdrt) in the form of neglect in the household at the Padang Police, what are the obstacles to legal protection for wives who are victims of criminal acts of domestic violence ) in the form of neglect in the household at the Padang Police, and how to overcome obstacles in legal protection for wives who are victims of criminal acts of domestic violence (kdrt) in the form of neglect in the household at the Padang Police. Legal protection for wives who are victims of criminal acts of domestic violence (kdrt) in the form of neglect in the household at the Padang Police is still not optimal because it has not been fully implemented in accordance with the rules in Law Number 23 of 2004 concerning the Elimination of Domestic Violence.